DAMPAK FITUR LIVE SHOPPING TIKTOK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION - Kristiawati, Sonia; Maulidina, Silvana; Eka Fujianti, Resya; Aqlimah Azeljilia Mumtaz, Nadia (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze the effect of the TikTok Live Shopping feature on purchase decisions for fashion products. This phenomenon reflects a shift in marketing from a transaction-based approach toward an interactive experience-based approach. The method used is a quantitative approach with an associative design involving 96 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed through classical assumption tests and simple linear regression analysis with the assistance of SPSS software. The results show that the TikTok Live Shopping feature has a positive and significant partial effect on purchase decisions, with a t-value of 14.812 (> 1.96) and a significance level of 0.000. The coefficient of determination (R²) of 0.693 indicates that this feature contributes 69.3% to influencing fashion product purchase decisions. Simultaneously, the regression model is declared significant with an F-value of 219.429. In conclusion, the integration of real-time interaction, entertainment, and transactional convenience within this feature is empirically proven to encourage and strengthen consumers’ purchase decisions